The Effects of Insect Infestation on Stored Agricultural Products and the Quality of Food - Ioannis G. Stathas; Anastasios C. Sakellaridis; Marina Papadelli; John Kapolos; Konstantinos Papadimitriou; George J. Stathas (Foods, 2023)
In this review article, we focus on the effects of insect pests on the quality of stored cereals and legume grains. The changes in the amino-acid content, the quality of proteins, carbohydrates, and lipids, and the technological characteristics of the raw materials when infested by specific insects are presented. The differences reported concerning the rate and kind of infestation effects are related to the trophic habits of the infesting insect species, the variation of the component distribution in the different species of grains, and the length of the storage period. For example, wheat germ and brans feeders such as Trogoderma granarium may cause a higher reduction in proteins than endosperm feeders such as Rhyzopertha dominica, since the germ and brans contain higher concentrations of proteins. Trogoderma granarium may also cause higher reduction in lipids than R. dominica in wheat, maize and sorghum, in which most of the lipids exist in the germ. Furthermore, infestation with insects such as Tribolium castaneum may downgrade the overall quality of wheat flour, by increasing the moisture content, the number of insect fragments, the color change, the concentration of uric acid, the microbial growth, and the prevalence of aflatoxins. Whenever possible, the significance of the insect infestation and the concomitant compositional alterations on human health are presented. It should be highlighted that understanding the impact of insect infestation on stored agricultural products and the quality of food will be crucial for the required food security in the future.